Circadian Phase and Its Relationship to Nighttime Sleep in Toddlers. (October 2013) - LeBourgeois, Monique K.; Carskadon, Mary A.; Akacem, Lameese D.; Simpkin, Charles T.; Wright, Kenneth P.; Achermann, Peter; Jenni, Oskar G.
Circadian phase and its relation to sleep are increasingly recognized as fundamental factors influencing human physiology and behavior. Dim light melatonin onset (DLMO) is a reliable marker of the timing of the circadian clock, which has been used in experimental, clinical, and descriptive studies in the past few decades. Although DLMO and its relationship to sleep have been well documented in school-aged children, adolescents, and adults, very little is known about these processes in early childhood. The purpose of this study was 1) to describe circadian phase and phase angles of entrainment in toddlers and 2) to examine associations between DLMO and actigraphic measures of children's nighttime sleep. Participants were 45 healthy toddlers aged 30 to 36 months (33.5 ± 2.2 months; 21 females). After sleeping on a parent-selected schedule for 5 days (assessed with actigraphy and diaries), children participated in an in-home DLMO assessment involving the collection of saliva samples every 30 minutes for 6 hours. Average bedtime was 2015 ± 0036 h, average sleep onset time was 2043 ± 0043 h, average midsleep time was 0143 ± 0038 h, and average wake time was 0644 ± 0042 h. Average DLMO was 1929 ± 0051 h, with a 3.5-hour range. DLMO was normally distributed; however, the distribution of the bedtime, sleep onset time, and midsleep phase angles of entrainment were skewed. On average, DLMO occurred 47.8 ± 47.6 minutes (median = 39.4 minutes) before bedtime, 74.6 ± 48.0 minutes (median = 65.4 minutes) before sleep onset time, 6.2 ± 0.7 hours (median = 6.1 hours) before midsleep time, and 11.3 ± 0.7 hours before wake time. Toddlers with later DLMOs had later bedtimes ( r = 0.46), sleep onset times ( r = 0.51), midsleep times ( r = 0.66), and wake times ( r = 0.65) (all p < 0.001). Interindividual differences in toddlers' circadian phase are large and associated with their sleep timing. The early DLMOs of toddlers indicate a maturational delay in the circadian timing system between early childhood and adolescence. These findings are a first step in describing the fundamental properties of the circadian system in toddlers and have important implications for understanding the emergence of sleep problems and the consequences of circadian misalignment in early childhood.